2018
DOI: 10.1146/annurev-pharmtox-010617-052832
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels as Potential Drug Targets

Abstract: The transient receptor potential (TRP) superfamily of channels comprises a diverse group of cation channels. Four TRP channel subunits coassemble to form functional homo- or heterotetramers that pass sodium, calcium, or both in the inward direction. Modulating TRP channel activity provides an important way to impact cellular function by regulating both membrane excitability and intracellular calcium levels. The import of these channels is underscored by the number of genetic diseases caused when they are mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
147
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 173 publications
0
147
0
1
Order By: Relevance
“…Regarding the potential of therapeutically targeting neuro-immune pathways, recent studies have shown that an anti-IL-31 receptor antibody, nemolizumab, successfully improves pruritus in patients with atopic dermatitis (77). Furthermore, ion channels play an essential role in the activation of sensory neurons, and TRP channel inhibitors are also promising candidates for various neuron-related symptoms and diseases (78). Neuropeptides, neurotransmitters, or their receptors are also potential targets for neuro-immune interaction, including VIP, CGRP, substance P, NMU, β2AR, and nAChR.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Regarding the potential of therapeutically targeting neuro-immune pathways, recent studies have shown that an anti-IL-31 receptor antibody, nemolizumab, successfully improves pruritus in patients with atopic dermatitis (77). Furthermore, ion channels play an essential role in the activation of sensory neurons, and TRP channel inhibitors are also promising candidates for various neuron-related symptoms and diseases (78). Neuropeptides, neurotransmitters, or their receptors are also potential targets for neuro-immune interaction, including VIP, CGRP, substance P, NMU, β2AR, and nAChR.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…TRP channels are activated and inhibited by a range of mechanisms, in response to thermal or chemical stimuli and/or mechanical forces (Venkatachalam and Montell, 2007). TRP channel mutations have been implicated in a number of different diseases (Nilius and Owsianik, 2010) and consequently are of interest as potential drug targets (Moran, 2018). Several TRP channels are modulated by membrane lipids (see for example (Fine et al, 2018;Wilkes et al, 2017;Yin et al, 2019), suggesting the possibility of lipid based therapies (Ciardo and Ferrer-Montiel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sophisticated physiological and ecological mechanisms have been developed through evolution to first detect and then adapt to ambient temperature (3)(4)(5). The transient receptor potential melastatin 8 (TRPM8) channel is the prototypical sensor for cold in vertebrates (6,7), which has been validated in both knockout mice (8) and pharmacological studies (9). However, how cold activates TRPM8 remains obscure.…”
mentioning
confidence: 99%